The director as a technology advocate: why? - Faust, Bill; Bailey, Mark (Henry Stewart Talks, 2021)
Holistic approach, Evolution of digital behaviour, Customer experience management (CEM) vs. customer relationship management (CRM), Insight based evolution, Volatility, Uncertainty, Complexity and Ambiguity (VUCA), Silos as a disadvantage, Partnership approach to tech, Disruption